2020
DOI: 10.1186/s40560-020-00444-5
|View full text |Cite
|
Sign up to set email alerts
|

Serial change of neutrophil extracellular traps in tracheal aspirate of patients with acute respiratory distress syndrome: report of three cases

Abstract: Background: Neutrophil extracellular traps (NETs) are fibrous structures released from activated neutrophils. NET formation has been reported to be associated with acute respiratory distress syndrome (ARDS). However, there are no reports dealing with serial changes of NET formation in tracheal aspirate of ARDS patients. Case presentation: We report three cases of ARDS. Case 1 is a 69-year-old man with necrotizing fasciitis of the buttocks, case 2 is a 49-year-old woman with extensive burns (80% of total body s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Activated neutrophils produce large quantities of S100A1 and A2, HMGB1 and free radicals. Furthermore, neutrophils release fibrous scaffolds containing DNA, histones, neutrophil elastase and myeloperoxidase that trap and kill pathogens, but also contribute to the development of acute respiratory distress syndrome 6,7 . To support their role, elevated neutrophil products have been identified in the sera of COVID-19 patients that correlate with clinical parameters such as C-reactive protein, D-dimer, and lactate dehydrogenase 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Activated neutrophils produce large quantities of S100A1 and A2, HMGB1 and free radicals. Furthermore, neutrophils release fibrous scaffolds containing DNA, histones, neutrophil elastase and myeloperoxidase that trap and kill pathogens, but also contribute to the development of acute respiratory distress syndrome 6,7 . To support their role, elevated neutrophil products have been identified in the sera of COVID-19 patients that correlate with clinical parameters such as C-reactive protein, D-dimer, and lactate dehydrogenase 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The literature showed that neutrophil counts are positively correlated with the degree of inflammation in ARDS (23). It has been reported that neutrophils and neutrophil-derived particles are significantly increased in bronchoalveolar lavage fluid of ARDS patients (24,25). Several studies have shown that during the occurrence of acute lung injury (ALI), neutrophils are the first immune cells to be recruited to inflammatory sites, after being stimulated by chemokines released from damaged lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Thus, there exists a greatly elevated neutrophilia in severe cases of COVID-19 which contributes to the ARDS. [ 21 22 ]…”
Section: Discussionmentioning
confidence: 99%